Characteristics of Ips Subjects - Rafelya Diningtias, Tahsa; Lestari Harahap, Annisa; Indriani Hasibuan, Fifi; Adam, Zulfitrah; Syahputra, Erwin; Yusnaldi, Eka (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Social Sciences (IPS) is one of the subjects taught from elementary school to junior high school. IPS examines a collection of events, facts, concepts and generalizations related to social problems. At junior high school level, social studies subjects include learning Geography, History, Sociology and Economics. Through social studies subjects, students are directed to become democratic Indonesian citizens, as well as global citizens who are responsible and love peace. The method used in this research is a literature review approach or literature study. Social Sciences (IPS) is a field of study, the same as Science, Mathematics and Indonesian. Thus, social studies as a field of study covers a variety of subjects. The scope of work includes the symptoms and problems of human life in society. The stress studied in Social Sciences is related to the phenomena and problems of social life, not focusing on theoretical and scientific knowledge, but on the reality of social life. Social Sciences is an academic field those studies, examines and analyzes social phenomena and problems in society by considering various aspects of life or a combination of both.